The influence of ground-granulated blast-furnace slag on geotechnical properties of jarosite waste - Gupta C.; Prasad A. (My University, 2025)
The rapid growth of industrial development sources the insufficiency of valuable land. Accordingly, it is the vibrant necessity to encourage the Research and Development works to attain ecological, financial, and societal benefits from colossal exploitation of their waste for worldwide benefits. The present work encourages the impact of pozzolanic waste material, i.e., ground-granulated blast-furnace slag (GGBS) in geotechnical characteristics of jarosite waste (zinc industries residual). The strength tests (unconfined compressive (UCS) and indirect tensile strength) were conducted on GGBS stabilized jarosite mixtures (GGBS, 10–30%) with different curing periods such as 7 days, 28 days, and 90 days. The outcomes illustrate that strength properties, increase by increase in GGBS percentage as well as curing periods. This strength improvement behavior of stabilized jarosite is also detected from the microstructural study (SEM), in which, denser agglomeration of GGBS stabilized jarosite particles, proves strength advancement. The durability studies (freeze–thaw (F-T)) of jarosite–GGBS mixtures were performed and it was observed that the loss in the UCS after five sequential F-T phases improved from 61.8% (raw jarosite waste) to 36.89, 26.60 and 17.12% with 10, 20, and 30% GGBS content, curing at 28 days period, respectively. The leachate study of jarosite indicates that jarosite contains hazardous constitutes, which were immobilized after stabilization with GGBS. From this study, it may be summarized that mixing of pozzolanic admixtures (GGBS) along with raw jarosite waste lead to a substantial enhancement in geotechnical properties with economic, social as well as environmental concern. © Springer Nature Singapore Pte Ltd. 2020.